HOW SOLAR ENERGY BECAME CHEAP pathways to a solar-centric economy. - Nemet, Gregory F. (ROUTLEDGE, 2026)
The climate problem is getting worse, but the solutions are getting better. So far, no technology has done more to improve the solutions available to address climate change than solar photovoltaics (PV). This revised edition describes an array of driving forces leading us toward a solar-centric energy system, one where solar power lies at the core rather than at the edge.Now in its second edition the book focuses on the future of solar, taking into account important changes since it was first published. It includes discussions on further growth and cost reductions, industrial policy, and grid integration of high solar. It has been fully revised to include the most recent data available, and includes two new chapters on India, the most important solar market in the Global South, and Australia, the fastest growing market for rooftop solar. The book concludes with a new chapter on a solar-centric economy. The costs of solar PV modules have reduced significantly since they were first commercialized and, in sunny places, are now cheaper than any other form of electricity. Drawing on developments in the US, Japan, Germany, Australia, India, and China, the book analyses the evolution and success of PV and asks how it can serve as a model for other low-carbon technologies, which require urgent innovation to address climate change.It will be of great interest to students and scholars of energy technology and innovation, climate change and energy analysis and policy, as well as practitioners and policymakers working in the energy industries.